An Investigation of Quaternary [5,3] Error Correcting Codes and their Implementation with Binary Devices - Rian, A.K.M. Toyarak; Dey, Partha Pratim; Elora, Farzana Karim (Journal of Informatics and Mathematical Sciences, 2015)
In this paper we investigate the existence, equivalence and some other features of quaternary error correcting codes. We also discuss the binary hardware devices that could be used to code and decode messages when these error correcting codes are used.